Dampak Pernikahan Dini Pada Kesehatan Mental Remaja: Scoping Review - Widya Rahayu; Silviatul Amalia; Juliana Safitri Ritonga (PT Nuansa Fajar Cemerlang, 2025)
Abstract: Early marriage frequently occurs in society and is often considered a normalized practice. The primary causes of early marriage include environmental or familial factors such as cultural norms, social pressure, poverty, and uncontrolled peer interactions. Marrying at a young age can raise concerns regarding marital issues due to a lack of mental readiness to start and maintain a healthy family life. Objective: This scoping review aims to explore and assess the impact of early marriage on adolescents. Methods: This study utilized the PRISMA-ScR Checklist, following five stages based on the Arksey and O’Malley framework. Article searches were conducted using four databases: PubMed, ScienceDirect, EBSCO, and Google Scholar. Results: Out of 10,864 articles identified, 11 met the inclusion criteria and were deemed relevant. This review highlights the impact of early marriage on adolescent mental health. Conclusion: The psychological consequences of early marriage are significant. Economic factors are a major determinant, as adolescents are often forced to assume financial responsibilities within the household, which strains their psychological well-being. Cultural beliefs that endorse early marriage as a means of controlling adolescent behavior further exacerbate mental health conditions. Domestic violence, insufficient capacity for autonomy, and limited awareness about reproductive health intensify the psychological burden, particularly among adolescent girls.